Root canal cleaning effectiveness with passive ultrasonic irrigation: A comparative in vitro study between Irrisafe and EndoUltra tip - Erlando Sartiono; Bernard Iskandar; Aryadi; Widijanto Sudhana (Wolters Kluwer Medknow Publications, 2021)
Background: Root canal irrigation has an important role in removing pulp tissue, dentine debris, and microorganisms in root canals. Passive ultrasonic irrigation (PUI) Irrisafe is a high-frequency wired ultrasonic device, which is usedto obtain cleanliness of root canal from cavitation and acoustic streaming. EndoUltra is a high-frequency wireless ultrasonic device. It has advantages in terms of its ease of application. However, further research is needed to identify the variations in effectiveness between PUI Irrisafe and EndoUltra tip for dentine debris cleanliness. Objective: The aim of this study was to determine the effectiveness between the activation of PUI Irrisafe and EndoUltra tip on the dentine debris cleanliness of the apical third of a root canal. Methods: This experimental study was carried out on 50 mandibular premolar teeth with a single root canal from extracted teeth. The teeth were irrigated with 5% NaOCl with the activation of EndoUltra # 20/02 (15 and 30 s), with 5% NaOCl with the activation of the PUI tip Irrisafe # 20/02 (15 and 30 s), or with conventional irrigation (30 s). The assessment of the dentine debris score was assessed by two observers using a scanning electron microscope (SEM). Analysis of the results used the Kruskal-Wallis and Mann-Whitney U tests. Results: Differences in median cleanliness scores for the apical third of the root canal from the Irrisafe group, the EndoUltra group, and conventional group had a Kruskal-Wallis test value of P = 0.005. The results showed that there were significant differences (P < 0.05) in five groups. Conclusion: PUI activation with the EndoUltra tip had a better effectiveness on the dentine debris cleanliness of the apical third of a root canal than the Irrisafe tip at 15 and 30 s.